2016
DOI: 10.5607/en.2016.25.6.342
|View full text |Cite
|
Sign up to set email alerts
|

Mildly Increased Mechanical Nociceptive Sensitivity in REV-ERBα Knock-out Mice

Abstract: Nociception is one of the most complex senses that is affected not only by external stimulation but also internal conditions. Previous studies have suggested that circadian rhythm is important in modulating nociception. REV-ERBα knock-out (KO) mice have disrupted circadian rhythm and altered mood-related phenotypes. In this study, we examined the role of REV-ERBα in inflammatory nociception. We found that the nociceptive sensitivity of KO mice was partially enhanced in mechanical nociception. However, this par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Accumulating evidence has shown that REV-ERBs negatively regulate the expression of various proinflammatory molecules such as the cytokine interleukin-6 (IL-6) and the chemokine CCL2, following binding of the synthetic REV-ERB-specific agonists GSK4112 and SR9009 in macrophages (Sato et al, 2014;. A previous finding showed mildly increased mechanical nociceptive sensitivity in REV-ERBα knockout mice (Lee et al, 2016). Furthermore, it is possible that REV-ERBs might be a new target as analgesic for osteoarthritisinduced pain (Das et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that REV-ERBs negatively regulate the expression of various proinflammatory molecules such as the cytokine interleukin-6 (IL-6) and the chemokine CCL2, following binding of the synthetic REV-ERB-specific agonists GSK4112 and SR9009 in macrophages (Sato et al, 2014;. A previous finding showed mildly increased mechanical nociceptive sensitivity in REV-ERBα knockout mice (Lee et al, 2016). Furthermore, it is possible that REV-ERBs might be a new target as analgesic for osteoarthritisinduced pain (Das et al, 2018).…”
Section: Introductionmentioning
confidence: 99%